EFEK LATIHAN FISIK TERHADAP KADAR MALONDIALDEHID PADA HEWAN MODEL PENUAAN - Indah Permata Sari1; Muhammad Ichwan; Yahwardiah Siregar (Jurnal Endurance, 2021)
Aging is a natural process that is characterized by decreased function. In the aging process a decline in the ability of reactive oxygen species. This causes damage to the membrane lipids that cause a decrease in function of the body's organs. Lipid oxidation process in the membrane because free radicals produce lipid peroxidation such as malondialdehyde which is used as a marker of oxidative stress. Regular physical exercise can overcome the negative effects of oxidative stress. To conduct studies on aging, animal models are used. One of the animal models used is the aging induction model by giving D-galactose. Metabolites from d-galactose can induce aging by causing oxidative stress. The purpose of this study was to determine the effect of physical exercise on reducing malondialdehyde levels in an aging animal model induced by D-galactose. This research was experimental in-vivo with a post test only research design. The research sample of 8 weeks old swiss webster mice, consisted of 10 treatment groups. The results of studies on animal models of aging induced D-galactose on malondialdehyde levels after being treated for 6 weeks from the statistical results obtained p value ≥ 0.05 was not significant. However, there was a significant decrease in MDA levels in the D-galactose + physical exercise group